Nutritional status of Syrian female migrants in Turkey: a cross- sectional study - Nurgül Arslan; Sema Çifci; Vasfiye Bayram Değer (International Journal of Public Health Science (IJPHS), 2023)
It is known that individuals who are immigrants experience malnutrition due to various reasons. The present study was conducted to compare the nutritional status of immigrant women, who arrive in Turkey from Syria, before and after migration, and to determine the factors that affect their current healthy eating index scores. The individuals participating in the study were recruited from Immigrant Health Unit in Mardin-Turkey. The sampling of this cross-sectional study consisted of the women who were between the ages of 15-49, 450 Syrian migrant women participated in the study. The data were collected with face-to-face interview technique and with a questionnaire that consisted of 2 parts. According to the Healthy Eating Index (HEI)-2015 score of the individuals mean was found to be 52.90±9.40. According to the hierarchical regression model, the monthly income, life expectancy in Turkey, body mass index (BMI), and the number of individuals in the family were statistically significant components to predict the mean HEI score. It was determined that the basic eating habits of individuals changed in the country of immigration, and more foods with high carbohydrate and saturated fat contents were consumed. It is required to design comprehensive studies and policies.